2021
DOI: 10.3390/ijerph18126331
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Nurses from Mistreatment by Patients: A Cross-Sectional Study on the Roles of Emotional Contagion Susceptibility and Emotional Regulation Ability

Abstract: In recent years, patient mistreatment of healthcare workers, especially nurses, has been frequent, endangering the interests of organizations while also threatening nurses’ own development. This study aims to examine from the perspective of nurses’ personal interests whether mistreatment by patients decreases nurses’ workplace well-being and career commitment, and how their susceptibility to emotional contagion and emotional regulation ability might mitigate these negative effects. This study adopted a cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…We also explored whether the moderating effect of organizational support on the relationship between the social sharing of negative events and emotional exhaustion depended on individual resilience. First, this study confirmed a significant positive correlation between nurses’ experiences of patient mistreatment and emotional exhaustion, which is consistent with previous studies [ 6 , 7 , 84 86 ]. The findings once again underscore the detrimental impact of patient mistreatment on nurses’ emotional and psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also explored whether the moderating effect of organizational support on the relationship between the social sharing of negative events and emotional exhaustion depended on individual resilience. First, this study confirmed a significant positive correlation between nurses’ experiences of patient mistreatment and emotional exhaustion, which is consistent with previous studies [ 6 , 7 , 84 86 ]. The findings once again underscore the detrimental impact of patient mistreatment on nurses’ emotional and psychological well-being.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that the most vulnerable healthcare workers victimized are nurses and paramedics [ 3 , 4 ], with the most common perpetrators being patients, their relatives, or visitors [ 5 ]. A recent survey of 4263 nurses in the healthcare sector showed that 54% of respondents had experienced verbal violence by patients [ 6 ], including negative emotional behaviors exhibited by patients or their families, such as anger, swearing, insults, yelling, and speaking rudely toward nurses [ 7 9 ]. All these negative emotional behaviors are known as “patient mistreatment”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al, 2022), sleep quality (Y. Liu et al, 2017), emotional contagion susceptibility (B. Liu et al, 2021), training and participation (Hu et al, 2018) did not moderate the relationship between mistreatment from customers and negative mood (γ = −0.14, p > .10), cognitive rumination (γ = 0.22, p = .35), social sharing of negative work events (γ = 0.19, p = .24), healthy food consumption (γ = 0.01, p < .05), emotional exhaustion (γ = 0.19, p > .05), workplace well-being ( β = .003, n.s .…”
Section: Resultsmentioning
confidence: 99%
“…This situation increases the likelihood of nurses transmitting emotions such as happiness, joy, disappointment, anxiety, fear, anger, stress, trust, etc. [7]. Since the emotions that nurses possess can impact nursing care and, particularly, negative emotions can jeopardize patient safety, it is emphasized that the susceptibility of nurses to emotional contagion and its consequences should be examined and managed effectively to prevent adverse outcomes [7][8].…”
Section: Introduction 1background Of the Studymentioning
confidence: 99%